2020
DOI: 10.1088/2053-1591/ab8b19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen embrittlement and non-metallic inclusions on tensile fracture properties of 55CrSi spring steel

Abstract: The tensile fracture behavior of 55CrSi spring steels were investigated. The results demonstrate that interior inclusion and hydrogen level has a significant effect on ductility and a minimal effect on tensile strength of the spring steel. It was due to the effect of cracking from MgO-Al 2 O 3 spinel inclusion or the inclusions with a mixture of CaO, SiO 2 and part of Al 2 O 3 due to hydrogen. The results of SEM showed that the ductility reduction is connected with the formation of 'fisheye' which formed under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Several other researchers have also reported similar types of features. 56,61,[63][64][65] It can be seen that the fish eye near the surface (Figure 5A) is comparatively more prominent than those found towards the center of the fracture surface, as shown in Figure 5D. Singh et al 61 observed a similar finding and reported that the variation in the size of fish eyes is attributed to a difference in hydrogen concentration at the respective location, which is consistent with the observation of the present study.…”
Section: Extended Finite Element Methods (Xfem) Reviewsupporting
confidence: 90%
See 1 more Smart Citation
“…Several other researchers have also reported similar types of features. 56,61,[63][64][65] It can be seen that the fish eye near the surface (Figure 5A) is comparatively more prominent than those found towards the center of the fracture surface, as shown in Figure 5D. Singh et al 61 observed a similar finding and reported that the variation in the size of fish eyes is attributed to a difference in hydrogen concentration at the respective location, which is consistent with the observation of the present study.…”
Section: Extended Finite Element Methods (Xfem) Reviewsupporting
confidence: 90%
“…As and when this pressure exceeds interatomic force under critical hydrogen concentration, crack initiates from these sites at a lower load than the uncharged specimen, showing reduced tensile strength. 56 Singh et al 61 and Li et al 64 reported that deep traps like inclusion cause degradation in the mechanical property of the material in the presence of hydrogen. The study by Fujita and Murakami 66 mentioned that debonding at the interface of inclusion and matrix causes void formation where the concentrated hydrogen causes cracking of GB at the edges of voids.…”
Section: Extended Finite Element Methods (Xfem) Reviewmentioning
confidence: 99%
“…Non-metallic inclusions have significant effects on many mechanical properties of suspension spring steel, including the strength, plasticity, toughness and fatigue properties. Li et al [23] studied the effect of inclusions on the tensile fracture properties of 55CrSi spring steel. The results demonstrated that interior inclusions have a significant effect on the ductility and a minimal effect on the tensile strength of spring steel.…”
Section: Introductionmentioning
confidence: 99%